The landsnail family Subulinidae (Gastropoda: Pulmonata) from Son La, Vietnam, with description of two new species - Sang, Do Duc; Nhuong, Do Van (Academia Journal of Biology, 2015)
The paper provided data on the landsnail family Subulinidae in Son La province, northwestern Vietnam. A total of nine species in three genera, viz., Allopeas Baker; 1935; Prosopeas Mörch, 1876 and Tortaxis Pilsbry, 1906 were recorded. Two new species are described, namely Prosopeas muongbuensis sp. n. from Muong Bu commune, Muong La district and Tortaxis comaensis sp. n. from Co Ma commune, Thuan Chau district. Prosopeas muongbuensis sp. n. is diagnosized by a cylindrical, medium-sized, thin, dextral, yellowish-brown shell; whorls convex and separated by an indented, relatively deep suture; callus thick and continued. Tortaxis comaensis sp. n. is recognized by a cylindrical, very large-sized, thick, yellowish-brown shell; whorls flatened and more coarsely ribbed; aperture subovate, oblique, with a thick peristome.